Mental well-being and fear: Examining the association between affective well-being and affective fear of crime in Finland - Kujala, Pietari; Niemelä, Mikko (Society of Social and Economic Research in the Universities of Turku, 2025)
There is a dearth of knowledge regarding the association between mental well-being and fear of crime. This study utilises several measures of well-being and fear to examine how poorer affective well-being is associated with affective fear of crime in Finland. In addition, the article explores the extent to which feelings of unsafety and generalised distrust moderate this association. The research comprised 2020 survey data representing the Finnish-speaking population in mainland Finland. Descriptive methods, median regression, and interaction terms are used for the analyses. These results indicate that poorer affective well-being is positively associated with a stronger affective fear of crime in Finland. Furthermore, feelings of unsafety and generalised distrust were found to moderate the considered association. This indicates that the perceived risk of victimisation facilitates the association between poorer affective well-being and stronger affective fear of crime in Finland.